Adverse effects of oral glucocorticoid therapy - a brief review of literature - Gruszka, Marta; Polańska, Paulina; Kubicka, Maria; Zakrocka, Martyna; Fick, Jakub (Journal of Education, Health and Sport, 2025)
Introduction and Objective: Glucocorticoids (GCs) are among the most commonly prescribed pharmaceuticals across various medical specialties. The purpose of this article is to provide an overview of the most common side effects of oral glucocorticoid therapy and to underline the importance of educating healthcare professionals and patients on this topic. State of knowledge: Glucocorticoids are commonly used in a wide range of patients because of their anti-inflammatory and immunosuppressive properties. Oral glucocorticoids can lead to a greater number of side effects in comparison with other routes of administration due to their systemic action. Adverse effects of glucocorticoid therapy involve endocrine, cardiovascular, musculoskeletal and central nervous systems. Patients often present with elevated serum glucose levels caused by reduced insulin sensitivity and amplified hepatic glucose production. Moreover, hyperglycemia and hypertension increase the risk of ischemic heart disease and heart failure. GCs impede bone formation and escalate bone resorption, resulting in bone mass reduction and osteoporosis. Myopathy may occur as a result of intensified catabolic processes. Glucocorticoid therapy impacts the production of cortisol by the adrenal glands and can lead to adrenal insufficiency and even adrenal crisis. Characteristic changes in external appearance aggravate self-esteem and mental health of patients resulting in decreased quality of life. Another adverse effect described in literature is substantial cognitive decline. Summary: Despite their multiple positive applications, glucocorticoids are associated with numerous side effects. It is imperative for medical professionals to ascertain that the disadvantages do not outweigh the advantages of glucocorticoid therapy. Further research is needed to ensure that patients are provided with the best possible care.